2018
DOI: 10.22317/jcms.03201811
|View full text |Cite
|
Sign up to set email alerts
|

PMSG and HCG hormones effect on the development and growth of ovarian follicles

Abstract: Objective Gonadotropins are generally used in animals and humans to stimulate ovulation and increase the number of available oocytes for techniques such as in vitro fertilization. Ovulation-inducing drugs are used to achieve multiple oocytes in one cycle, thereby increasing the chances of pregnancy in patients with infertility. The aim of this study was to evaluate the effect of gonadotropins on stimulation of ovulation and their inductive role on the growth and development of follicles in the ovary. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…While both PMSG and LHRHa can induce estrus synchronization, our study showed they have different effects on fetal development. PMSG has primarily FSH-like and LH-like activity in non-equids 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…While both PMSG and LHRHa can induce estrus synchronization, our study showed they have different effects on fetal development. PMSG has primarily FSH-like and LH-like activity in non-equids 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%